IMPLEMENTASI MANAJEMEN “RE” UNTUK MENGURANGI JAM KOSONG SERTA KETERLAMBATAN GURU DATANG DAN MASUK KELAS DI SD NEGERI 163099 - Nurmala Tampubolon (FIP Unimed, 2017)
ABSTRACTThe purpose of writing to reduce school hours, reduce the number of teachers who are late in school, reducing the number of teachers who are late to class. The cycle pattern that the authors offer starts from the control, improvement/improvement, maintenance, action, planning, inspection and implementation. Control needs to be done on input products, process work (KBM) or PBM implementation until the end of output. Therefore, it is necessary to develop a